Paleoeskimo Dogs of the Eastern Arctic - Morey, Darcy F.; Aaris-Sørensen, Kim (ARCTIC, 2002)
Sled or pack dogs have been perceived as an integral part of traditional life in the Eastern Arctic. This perception stems from our knowledge of the lifeway of recent Thule and modern Inuit peoples, among whom dog sledding has often been an important means of transportation. In contrast, the archaeological record of preceding Paleoeskimo peoples indicates that dogs were sparse at most, and probably locally absent for substantial periods. This pattern is real, not an artifact of taphonomic biases or difficulties in distinguishing dog from wolf remains. Analysis of securely documented dog remains from Paleoeskimo sites in Greenland and Canada underscores the sporadic presence of only small numbers of dogs, at least some of which were eaten. This pattern should be expected. Dogs did not, and could not, assume a conspicuous role in North American Arctic human ecology outside the context of several key features of technology and subsistence production associated with Thule peoples. On a toujours considéré les chiens de traîneau ou chiens de somme comme faisant partie intégrante de la vie traditionnelle dans l'Arctique oriental. Cette perception vient de nos connaissances sur le mode de vie des derniers Thulés et des Inuits modernes, chez qui le traîneau à chiens a souvent représenté un mode de transport majeur. En revanche, les données archéologiques des peuples paléoesquimaux qui ont précédé Thulés et Inuits révèlent que les chiens étaient tout au plus clairsemés, et probablement absents localement pendant de longues périodes. Cette répartition est bien réelle et n'est pas le produit de distorsions taphonomiques ou de difficultés à faire la distinction entre les restes du chien et ceux du loup. L'analyse de restes canins proprement documentés trouvés sur des sites paléoesquimaux au Groenland et au Canada souligne la présence sporadique de chiens en nombre toujours restreint, dont au moins quelques-uns étaient mangés. Cette répartition n'est pas surprenante, les chiens n'assumant pas - et ne pouvant assumer - un ...